2016
DOI: 10.3390/ma9030181
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Conjugated Polymer Side Chain Manipulation on the Efficiency and Stability of Polymer Solar Cells

Abstract: The stability of polymer solar cells (PSCs) can be influenced by the introduction of particular moieties on the conjugated polymer side chains. In this study, two series of donor-acceptor copolymers, based on bis(thienyl)dialkoxybenzene donor and benzo[c][1,2,5]thiadiazole (BT) or thiazolo[5,4-d]thiazole (TzTz) acceptor units, were selected toward effective device scalability by roll-coating. The influence of the partial exchange (5% or 10%) of the solubilizing 2-hexyldecyloxy by alternative 2-phenylethoxy gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Moreover, intermediate oxidizing product also showed antioxidant properties . Bundgaard et al demonstrated that various side chains of active materials can also greatly influence device stability. They found that the photochemical stability of the polymer film was improved by partially exchanging 2‐hexyldecyl side chain with 2‐hydroxyethyl group on BDT unit, where exchanging 10% of 2‐hydroxyethyl or 2‐phenylethyl side chain exhibited the best device stability.…”
Section: Stability Of Active Layer Materialsmentioning
confidence: 99%
“…Moreover, intermediate oxidizing product also showed antioxidant properties . Bundgaard et al demonstrated that various side chains of active materials can also greatly influence device stability. They found that the photochemical stability of the polymer film was improved by partially exchanging 2‐hexyldecyl side chain with 2‐hydroxyethyl group on BDT unit, where exchanging 10% of 2‐hydroxyethyl or 2‐phenylethyl side chain exhibited the best device stability.…”
Section: Stability Of Active Layer Materialsmentioning
confidence: 99%
“…These results show an absence of phase separation and crystallization as well as an enhancement in the long-term stability of the solar cell parameters, as shown in Figure 3d for samples stored in nitrogen at 85 o C temperature. [34] However, the adoption of this concept on advanced conjugated polymers (like polymers based on BT or thiazolothiazole) using the phenethyl group to partially exchange the solubility side chain, did not lead to a clear enhancement of the stability of the BHJ PSCs [35]. This means that this approach cannot be applied to all suitable advanced conjugated backbones for PSCs.…”
Section: Chemical Diversification Of the Side Chain Of The Light Absomentioning
confidence: 99%
“…Owing to their environmental and thermal stability, polythiophene derivatives such as alkyl-substituted poly­(thiophene)­s, and in particular P3HT, have been widely studied . The crystallization behavior of polythiophene derivatives can be improved through side-chain engineering. Crystallization of poly­(3-(2,5-dioctylphenyl)­thiophene) (PDOPT) was facilitated by the attachment of sterically demanding side chains to the polythiophene backbone, leading to an easily planarizable polymer. , As a further result of such side-chain engineering, the properties of PDOPT improved remarkably, , for example, yielding a lower melting temperature compared to other polythiophene derivatives , and exhibiting high PL quantum yields. , Upon photoexcitation, the chains of conjugated polymers such as PDOPT may experience torsional changes and potentially become more planarized. , Furthermore, in such systems, torsion around monomer–monomer bonds may cause bending and stretching of these linking bonds. Accordingly, chains may stretch and thus potentially get aligned, thereby increasing the order .…”
Section: Introductionmentioning
confidence: 99%